Worker information system to support during complex and exhausting assembly of high-voltage harness - Fischer, Christian; Bönig, Jochen; Franke, Jörg; Lusic, M.; Hornfeck, R. (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
There are a lot of different kinds of electric drives and each category has a different installation position within a vehicle. A huge number of variants pose a challenge for manual assembly as the varying constellations of high-voltage (HV) cables require individual assembly steps. A worker needs information both about a vehicle and about HV components with their properties. We obtained good results for this on base of a worker information system (WIS). We can visualize parts assembly using three-dimensional (3-D) objects. The results of hazard analysis are shown in text format. But a WIS lacks in representing the physical behavior of parts within assembly. Especially HV cables move in an undetermined way when they are handled. We have an approach to simulate HV cables within assembly simulation. The material properties of HV cables during distortion are calculated in a finite element analysis (FEA). These parameters flow into an assembly simulation containing flexible parts like HV cables and a digital human model. The results of simulation runs can not only be used for assembly planning but also for worker guidance. We present an approach how to qualify simulation results for import to a WIS. In addition, possible application scenarios for such a WIS are explained.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly Technologies; Worker Information System